An unusual case of hyperlactataemia in a neonate. (December 2013) - Nirupam, Nilay; Nangia, Sushma; Kumar, Ajay; Saili, Arvind
We report a HIV uninfected neonate born to HIV positive mother, who had tachypnoea at birth. On investigations, he was found to have hyperlactataemia. All the secondary causes for elevated lactate were ruled out. Hyperlactataemia was attributed to the perinatal exposure, to maternal antiretroviral (ARV) drugs, mainly nucleoside analogues. Asymptomatic and symptomatic hyperlactataemia is not uncommon in HIV-exposed infants. Neonates with tachypnoea, who are HIV- and ARV-exposed with no obvious cause, should be screened for raised arterial lactate.